2020
DOI: 10.1002/lio2.445
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing nasal obstruction and its common causes using the nasal acoustic device: A pilot study

Abstract: Objectives: There is a need to develop a medical device which can accurately measure normal and abnormal nasal breathing which the patient can better understand in addition to being able to diagnose the cause for their nasal obstruction. The aim is to evaluate the accuracy of the nasal acoustic device (NAD) in diagnosing the common causes for nasal obstruction and diagnosing normal and abnormal (nasal obstruction) nasal breathing. Methods: This pilot study recruited 27 patients with allergic rhinitis (AR), chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We first introduced the NOBI concept in a pilot study using the nasal acoustic device to diagnose nasal obstruction (NO). 20 Here we demonstrated that the NOBI model could be applied to NIPF measurements and nasal acoustic scores. The NOBI values were used to identify the presence of a deviated nasal septum (DNS) with a sensitivity of 68% using NIPF and 77% using NAD acoustic scores.…”
Section: Key Findingsmentioning
confidence: 80%
See 1 more Smart Citation
“…We first introduced the NOBI concept in a pilot study using the nasal acoustic device to diagnose nasal obstruction (NO). 20 Here we demonstrated that the NOBI model could be applied to NIPF measurements and nasal acoustic scores. The NOBI values were used to identify the presence of a deviated nasal septum (DNS) with a sensitivity of 68% using NIPF and 77% using NAD acoustic scores.…”
Section: Key Findingsmentioning
confidence: 80%
“…We first introduced the NOBI concept in a pilot study using the nasal acoustic device to diagnose nasal obstruction (NO) 20 . Here we demonstrated that the NOBI model could be applied to NIPF measurements and nasal acoustic scores.…”
Section: Discussionmentioning
confidence: 99%
“…Despite development of techniques to measure nasal obstruction, such as nasal inspiratory peak flow (NIPF), Andrews et al demonstrated that improvement in NIPF does not necessarily correlate with improved selfreported functional outcomes. 20 Although studies are underway to further evaluate novel methods of assessing nasal obstruction quantitatively, such as acoustic rhinometry, 21 there is currently no consensus as to how this should best be measured and documented. This therefore means that patient-reported outcome measures, such as SNOT-22, NOSE, and FACE-Q, remain the mainstay of postoperative evaluation of surgical success.…”
Section: Discussionmentioning
confidence: 99%
“…The CRS patient group exhibited a lower percentage change in unilateral nasal inspiratory peak flow (uNIPF) after applying nasal decongestant compared to the non-CRS group. Conversely, the AR patient group showed an opposite trend 5 .…”
Section: Introductionmentioning
confidence: 88%